Patriarchy and Resistance in Anita Desai's Fasting, Feasting - Dr. B M Badiger (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2026)
The novel focuses on gender inequality through Uma's oppression by male power and family prospect, contrasted against the rights enjoyed by her brother, Arun. This paper highlights the ironically denunciated the patriarchal common formation and endangered them. The novel fasting and feasting is about a common clash found along with the exacting roles assigned by society to men and women. This paper also enhances perfect portrayal of a patriarchal society in which the father is the main figure of the house and who leads every decision in the house. Patriarchy is methodically a set of rules in which a male domination over a female in every aspect of life.